Analyzing the Evolution and the Future of the Internet Topology Focusing on Flow Hierarchy - Nakata, Yu; Arakawa, Shin’ichi; Murata, Masayuki (Journal of Computer Networks and Communications, 2015)
In the Internet, Autonomous Systems (ASes) exchange traffic through interconnected links. As traffic demandincreases, more traffic becomes concentrated on such links. The traffic concentrations depend heavily on the globalstructure of the Internet topology. Therefore, a topological evolution considering the global structure is necessary tocontinually accommodate future traffic amount. In this paper, we first develop a method to identify the hierarchicalnature of traffic aggregation on the Internet topology and use this method to discuss the long-term changes in trafficflow. Our basic approach is to extract the “flow hierarchy,” which is a hierarchical structure associated with trafficaggregation. Our results show that the current connection policy will lead to a severe traffic concentration in the future. We then examine a new evolution process that attempts to reduce this traffic concentration. Our proposed evolutionprocess increases the number of links in the deeper level in the hierarchy, thus relaxing the traffic concentration. Weapply our evolution process to the Internet topology in 2000 and evolve this scenario over 13 years. The resultsshow that our evolution process could reduce the traffic concentration by more than half compared with that withoutour evolution process.